2010
DOI: 10.1111/j.1365-2559.2010.03596.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases, TIMPs and growth factors regulating ameloblastoma behaviour

Abstract: These results suggest an interplay involving growth factors MMPs and TIMPs that may contribute to ameloblastoma behaviour. Signals generated by this molecular network would be transduced by ERK 1/2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 33 publications
4
49
1
4
Order By: Relevance
“…Aberrant MMP activity in tumor cells and surrounding stromal tissues has been implicated in tumor invasion and metastasis. According to studies on in vitro and in vivo tumor invasiveness, therapeutic interventions that inhibit MMP activity appear to be very promising [16]. In the present study, no difference was observed in the expression of MMP-9 between ameloblastoma and AOT.…”
Section: Discussioncontrasting
confidence: 44%
“…Aberrant MMP activity in tumor cells and surrounding stromal tissues has been implicated in tumor invasion and metastasis. According to studies on in vitro and in vivo tumor invasiveness, therapeutic interventions that inhibit MMP activity appear to be very promising [16]. In the present study, no difference was observed in the expression of MMP-9 between ameloblastoma and AOT.…”
Section: Discussioncontrasting
confidence: 44%
“…Similarly, the staining percentage was less pronounced in the epithelial and stromal components of ameloblastoma compared with the other lesions, a finding suggesting higher production of MMP-9, increased BM degradation and the consequent higher invasion potential of this tumor. Siqueira et al 32 observed intense and diffuse TIMP-2 staining in ameloblastomas, which was associated with lower aggressiveness of the tumor. In an in vitro study, Wang et al 5 showed that overexpression of TIMP-2 in ameloblastoma cells was associated with the suppression of MMP-2 activity and a consequently lower invasion potential.…”
Section: Discussionmentioning
confidence: 97%
“…MMP-9 is known for mediating degradation of basement membrane and remodeling of ECM. Studies have provided compelling evidence that MMP-9 is involved in tumor growth and bone metastases [8,[12][13][14][17][18][19][20][21]. According to Vicente et al [17] MMP-2 and MMP-9 are involved in angiogenesis and tumor growth, suggesting an association of the gelatinases with aggressive behavior and unpredictable clinical course in some human neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is also considered to have an important role in bone resorption and is closely related with several osteodestructive pathologies. [8,20,21]. MMP-9 act not only as solubilizers of bone matrix but also as regulators of the initiation of bone resorption [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation